Optimalisasi Ukuran Maksimum Agregat terhadap Workability dan Kuat Tekan Beton Mutu Tinggi dengan Tambahan Superplasticizer - Farhandasi, Reza; Maulidin, Alpin; Khairunnisa, Hanyta; Rahmadhani, Yuni (Jurnal Teknologi, 2026)
The demand for High-Strength Concrete (HSC) in modern infrastructure necessitates the optimization of its constituent materials. This study investigates the effect of varying Maximum Aggregate Size (MAS) on the compressive strength of HSC, which was designed with a low water-cement ratio (0.4) and a target characteristic strength (f’c) of 40 MPa at 28 days, utilizing a superplasticizer to maintain workability. Three variations of coarse aggregate size were tested: 19.10 mm, 25.56 mm, and 31.50 mm. Twenty cube specimens (15×15×15 cm) were prepared and tested. The results showed a clear inverse correlation between MAS and compressive strength. The 19.10 mm aggregate produced the highest average strength of 30.269 MPa, followed by 29.110 MPa (25.56 mm) and 27.322 MPa (31.50 mm). This optimal performance is attributed to the superior gradation (lowest Fineness Modulus) and the resulting enhancement of the Interfacial Transition Zone (ITZ) quality, as smaller aggregates promote a denser and stronger bond with the cement paste. Although the target strength of 40 MPa was not achieved, the 19.10 mm aggregate demonstrated the highest potential for strength development, showing a 10.79% increase compared to the 31.50 mm aggregate. The study concludes that MAS 19.10 mm is the most optimal size among the variations tested for maximizing compressive strength under the given mix design.